KEBIJAKAN DIVIDEN MEMODERASI HUBUNGAN ANTARA UKURAN PERUSAHAAN DAN PERPUTARAN ASET TERHADAP HARGA SAHAM - Riyandi, Achmad Rizki; Nuryani, Anum (UNIVERSITAS DHARMAWANGSA, 2025)
The fluctuating stock price of PT United Tractors Tbk reflects challenges for investors, even though the company is large and has significant assets, indicating the need for an examination of the influence of company size and asset management efficiency (TATO) on share prices. Dividend policy also plays a role in boosting investor confidence, maintaining stock price stability, and is the focus of research using historical data from 2004 to 2023 in the heavy equipment and mining industry. This study aims to analyze the influence of company size and Total Asset Turnover (TATO) on the share price of PT United Tractors Tbk during the period 2004–2023, as well as to examine the moderating role of dividend policy. The data were analyzed using multiple linear regression and moderation regression analysis, including classical assumption tests as prerequisites before regression. The multiple regression results show that company size. These findings indicate that although company size and TATO positively affect stock prices, dividend policy negatively moderates this relationship.